Körsångares erfarenheter av informellt ledarskap i körstämman - Zadig, Sverker; Lyberg-Åhlander, Viveka; Folkestad, Göran (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2017)
Through interviews with choral conductors and recordings of individual singers, previous studies have demonstrated choral singers acting as informal musical leaders. The purpose of the present study was to investigate singers’ awareness of informal musical leaders and how the singers relate to this informal leadership. With focus-group interviews, using Stimulated recall as a method, choir singers have reacted to recorded material from rehearsals and concerts. A motet choir, a female choir and a professional vocal ensemble provided the strategic selection for the collection of data. The results show that the singers to different degrees are aware of their own positions as leaders or followers. Most of them had a clear idea of who acted as a musical leader, and some were unaware of their own leadership. Furthermore, it was found that those who took the role as followers could change and become leaders. One conclusion of the study is that, in order to improve choral work, it may be worthwhile to make choral singers aware of the existence of musical leadership in choirs. This might help and guide choral conductors and singers in their work to develop choirs both in precision, articulation and choral blend, aspects that can be controlled by the informal musical leaders.